Effects of low-load blood flow restriction on the venous system in comparison to traditional low-load and high-load exercises - Franz, Alexander; Ji, Sanghyeon; Fröschen, Frank Sebastian; Kerstin, Marleen; Wahl, Patrick; Behringer, Michael (Frontiers in Physiology, 2023)
Purpose: Blood-Flow-Restriction (BFR) training provides the ability to achieve hypertrophy effects even though only light mechanical loads are applied. However, its impact on venous pressures and function are still unknown. Therefore, the present study investigates the influence of BFR-training on intravascular venous pressure and venous function in comparison to control exercises with low or high mechanical loads. Methods: In a randomized cross-over design, ten healthy men (27.6 ± 6.4 years) underwent three trials of unilateral knee-extensor exercise with three different training protocols, low-load- (LL-RT, 30% of the individual 1-repetition-maximum, 1RM), low-load BFR- (LL-BFR-RT, 30% 1RM, 50% limb occlusion pressure, LOP) and high-load resistance exercise (HL-RT, 75% 1RM). Exercise protocols contain about four sets of knee extension exercise (Range-of-Motion: 0-0-95°), separated by 60 s of rest. Each set was performed until volitional muscle failure. For analysis of changes in intravascular venous pressures and venous function, a venous catheter was placed at the exercising leg before each trial. Whereas venous pressures were recorded throughout the exercise trials, phlebodynamometric investigations were performed before and after each trial. Furthermore, subjective pain perception during and after exercise was accessed by visual analogue scale. One-way ANOVA was used to assess mean differences between training protocols, while two-way repeated-measures ANOVA (rANOVA; time x condition) was performed to compare changes in measures over time among conditions. Data were given as means ± standard deviation (SD). Results: In comparison to the exercise trials without venous occlusion, total workload was significantly lower in the LL-BFR-RT (LL-RT: 1745 ± 604 kg vs LL-BFR-RT: 1274 ± 237 kg vs HL-RT: 1847 ± 367 kg, p = 0.004) without indicating statistical differences in venous pressures during the exercise sets (interaction: p = 0.140) or pain perception (interaction: p = 0.574). Similarly, phlebodynamometric assessment of venous function (e.g. refill-time of the venous system pre-vs. post exercise trials–LL-RT: 29.7 ± 11.0 s vs 25.5 ± 9.6 s, LL-BFR-RT: 26.6 ± 13.0 s vs 27.3 ± 13.8 s, HL-RT: 25.9 ± 10.9 s vs 23.1 ± 8.2 s) revealed no time (p = 0.156), condition effect (p = 0.802) or their interactions (p = 0.382). Conclusion: The present study is the first one describing the acute effects of LL-BFR-RT to muscle failure on venous pressures and function in comparison to a LL- and HL-RT in the lower limbs. In contrast to the existing literature, LL-BFR-RT does not elevate the venous pressures during exercise higher than a comparative exercise without BFR and does not show any adverse effects on venous function after the exercise.